Architectural Design Procedures - Edward Arnold; Thompson Arthur (1990)
Preface, Acknowledgements, Setting the Scene, Background to Architectural Practices, Organisation and Business Side of Architectural Practices, Architects and the Law, Technical Information, General Office Practice, Design Constraints, Design Procedures Generally, Pre-Contact Procedures Generally, Pre-Contact Procedures Generally, Contract Stages, Standard Documentation, Word Phrases and Abbreviations, Questions, Bibliography, Recommended Reading, Index.
Preface, Acknowledgements, Setting the Scene, Background to Architectural Practices, Organisation and Business Side of Architectural Practices, Architects and the Law, Technical Information, General Office Practice, Design Constraints, Design Procedures Generally, Pre-Contact Procedures Generally, Pre-Contact Procedures Generally, Contract Stages, Standard Documentation, Word Phrases and Abbreviations, Questions, Bibliography, Recommended Reading, Index.